Triterpenoids and phenolic compounds from Euphorbia tithymaloides L. (Euphorbiaceae) - Trang, Vu Minh; Hien, Pham Thu; Nam, Vu Hoang; Son, Phan Tong; Giang, Phan Minh (Vietnam Journal of Chemistry, 2014)
Friedelan-3b-ol (1), b-sitosterol (2), oryzanol-C (3), 2,4,6-trimethoxyacetophenone (4), 3,4,3’-tri-O-methylellagic acid (5), scoparone (6), hopenone B (7), and tetradecane-1,2-diol (8) were isolated from the leaves and stems of Euphorbia tithymaloides L. (Euphrobiaceae) collected in northern Vietnam. Their structures were determined by spectroscopic analysis. Keywords: Euphorbia tithymaloides, Pedilanthus tithymaloides, Euphorbiaceae, triterpenoid, phenolic compound.